Martha Stewart's cookies : the very best treats to bake and to share / Martha Stewart, Victor Schrager - Stewart, Martha
Provides nearly two hundred recipes for cookies of all shapes, sizes, and textures, as well as tips on tools, techniques, and packaging ideas.